Dinosaur time - Foreman, Michael, 1938- (London : Andersen Press, 2002)
Tom disobeys his mother when she tells him not to play with her new kitchen timer and finds himself transported to a time when dinosaurs are alive.
4.2
K-3
Keywords: Dinosaurs -- Fiction; Time travel -- Fiction; Dinosaurs -- Fiction; Time travel -- Fiction